Drivers of the Load Capacity Factor in New İndustrialized Countries: Economic Growth, Financial Development and Urbanization on Load Capacity Factor - Durmus, Savas; Batu Agırkaya, Melahat; Akyol, Hikmet (International Journal of Economics and Financial Issues, 2025)
This study examines the effects of economic growth, financial development, and urbanization on the load capacity factor (LCF) for Newly Industrialized Countries (NICs) over the period 1991-2021. In this context, we analyzed the relationship between the variables using the Fixed Effects Driscoll-Kraay and Fixed Effects Panel Quantile estimators. The estimation results indicate that across all quantiles (low, medium, and high levels of environmental degradation), economic growth has a positive effect on LCF, while the squared term of economic growth has a negative effect. Urbanization and renewable energy consumption positively impact LCF, whereas financial development and labor force participation rates have negative effects. The positive effects of urbanization and renewable energy consumption on LCF become more pronounced in higher quantiles. Conversely, the negative impact of labor force participation on LCF is stronger in higher quantiles. The negative effect of financial development on LCF, however, becomes statistically insignificant at higher quantiles.